Assessing the Effectiveness of the Halal Assurance System 23000 - Muchammad Fauzi; Dede Rodin (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2024)
This study addresses the limited empirical understanding of how the Halal Assurance System (HAS 23000) is implemented in practice and how far halal-certified slaughterhouses are institutionally prepared to ensure sustainable halal meat availability. The study aims to examine the implementation of HAS 23000 and assess the readiness of slaughterhouses in supporting halal meat assurance. Using field research with a descriptive qualitative approach, the study relies on primary data obtained through interviews, observations, and questionnaires, complemented by secondary data from official documents and regulations, with analysis centered on the eleven HAS 23000 criteria. The results indicate that HAS 23000 has been implemented at a relatively satisfactory level, with compliance rates ranging from 60% to 100% across all eleven criteria, including halal policy, halal management team, training and education, materials, products, production facilities, written procedures for critical activities, traceability, handling of non-compliant products, internal audits, and management reviews. Halal-certified slaughterhouses primarily operate as providers of halal slaughtering services in collaboration with livestock farms and beef suppliers, while several have diversified their activities by establishing halal meat outlets to strengthen supply continuity. Active coordination and communication with relevant stakeholders further support the stability of halal meat supply. The findings imply that while technical compliance with HAS 23000 is generally adequate, improvements are still needed in strengthening managerial commitment, documentation, and capacity building, particularly in auditing and continuous monitoring, to enhance the effectiveness and sustainability of halal assurance systems.